EFFECTS OF CHINESE HERBAL RECIPES ON IMMUNITY IN IMMUNOSUPPRESSIVE MICE - Bao, Yongzhan; Jing, Cui; Shi, Wanyu (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The Chinese herbal formula consisting of Astragalus membranaceus, Epimedium brevicornum, Paeoniae Alba Radix and Radix Ophiopogonis in proper proportions were adopted in order to investigate the immunoenhancing properties of the herbal formula. Fifty ICR mice were randomly divided into 5 groups (NS,NS+Hy,L+Hy,M+Hy,H+Hy ). The mice in hydrocortisone (Hy) groups were injected with hydrocortisone i.p. to induce the immunosuppressive condition. The mice in group NS were administered with normal saline as controls. The mice in groups NS+Hy,L+Hy,M+Hy,H+Hy were administered with normal saline, low, moderate and high dose of the herbal prescription respectively by gavage for 6 days. The level of serum hemolysin, the function of antibody function cell(AFC)and CD4+/CD8+ T cell ratio were measured at the end of experiments. The results showed that the level of serum hemolysin, the function of AFC and CD4+/CD8+ T cell ratio in L+Hy,M+Hy,H+Hy groups increased significantly compared with those in NS or NS+Hy groups. These results indicate that Chinese herbal medicine prescription can enhance humoral immunity and cellular immune function of the immunosuppressive mouse.